Selftest by μC to detect faulty capacitors - Can, Yavuz; Rantisi, Mohammed; Sattler, Sebastian (Scientific Cooperations Publications, 2013)
The presented work concerns the concept of validating measurements of simple analog filter  wirings in automotive electronic control units (ECU). Therefore, open or faulty capacitors should be detected. An input signal is fed to the filter circuit by means of the microcontroller TC1797, and the filter output signal for determining the functionality of the filter is received by the same microcontroller.
Keywords: Verification; µC 1797; ECU; signal theory; filter analysis